MEANING DIFFERENCES BETWEEN TWO QURAN TRANSLATIONS IN ACTIVISM ERA IN INDONESIA (IDEOLOGY IN TRANSLATION ANALYSIS) - Betty Maulirosa Bustam; Rika Astari (Analisa: Journal of Social Science and Religion, 2018)
This article attempts to investigate the influence of ideology concept in Quran translations in Indonesia. The extent to which the ideology can influence the translators’ style and choice of words that will shape the receivers’ worldviews. In the lead up to Indonesian independence, when young Muslim intellectuals began to be moved to understand their religion well, so as not to be regarded as an underdeveloped religion, two translations appear: De Heilige Qoer-an by Maulana Muhamamad Ali and Tafsir Quran Karim by Mahmud Yunus. The two translations have similarities in the writing of a modern style. Both also attempt to translate the Quran in line with the development of science, and assume there is no dispute between revelation and creation, so the works are favored by Indonesian Muslim intellectuals. However, although they have the same concept of translation, many verses are translated differently, especially the verses about the miracles of the prophets and the privileges of Isa (as). The differences are noticeable; this is much related to the ideology background of the two translators. De Heilige Qoer-an brings Ahmadiyya ideology while Tafsir Quran Karim holds to the opinion of the prominentscholars, including the scholars of Indonesia.